1995
DOI: 10.1093/oxfordjournals.humrep.a136320
|View full text |Cite
|
Sign up to set email alerts
|

Partial hydatidiform mole and hypertension associated with a live fetus--variable presentation in two cases

Abstract: Partial hydatidiform mole associated with live births is a rare condition. There are not enough cases in the literature to allow the assessment of comprehensive risks to be made and upon which management policies can be based. Several clinical dilemmas arise following diagnosis of a viable pregnancy associated with molar tissue. We present two cases demonstrating the problems and suggest management based on outcome and a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In our patient, placentomegaly and high levels of β-hCG accompanied the development of preeclampsia. This is consistent with the reported series of Rijhsinghani et al [3] and two other case reports of triploid twin pregnancies complicated by preeclampsia [4,6]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our patient, placentomegaly and high levels of β-hCG accompanied the development of preeclampsia. This is consistent with the reported series of Rijhsinghani et al [3] and two other case reports of triploid twin pregnancies complicated by preeclampsia [4,6]. …”
Section: Discussionsupporting
confidence: 93%
“…In three cases [4]-[6] of five concerning a triploid fetus and a healthy co-twin, a therapeutic abortion was performed, two of which were for severe preeclampsia. There are only two cases reported with survival of the healthy co-twin, both after selective abortion of the triploid fetus.…”
Section: Introductionmentioning
confidence: 99%
“…From this clinical perspective there are two different type of gross pathology that can affect the placenta, focal degeneration and diffuse partial degeneration. (12,15,16,17) Molar pregnancy with co-existing normal live foetus has been divided into three types. The first and most common is twin pregnancy with one normal fetus having a normal placenta and another complete mole, second type is a twin pregnancy with normal fetus and the placenta and another partial mole.The third and most uncommon occurrence is a singleton normal fetus with partial molar placenta 13 similar to our case.…”
Section: Discussionmentioning
confidence: 99%
“…Nwosu et al reported that no reports demonstrate that if pregnancy is kept to term, it will increase the incidence of invasive mole or choriocarcinoma. 15 Zahida P et al from Pakistan, reported G4 P1 + 2 lady with partial mole along with alive baby managed conservatively 18 weeks onward and delivered successfully at term. 16 Hsieh CC et al from Department of Obstetrics and Gynecology, Taiwan, Republic of China, reported delivery of a severely anemic fetus after partial molar pregnancy.…”
Section: Pregnancymentioning
confidence: 99%